INVENTARISASI TANAMAN MPTS (MULTY PURPOSE TREE SPECIES) DI DAERAH TANGKAPAN AIR DANAU TOBA PROVINSI SUMATERA UTARA - Samuel Marpaung; Afifuddin Dalimunthe; Budi Utomo (Program studi Kehutanan USU, 2015)
This research aims to determine the types of MPTS, silvicultural techniques, plant benefits, the role of plant MPTS and peoples perception if the plant MPTS used as plant rehabilitation. This research was conducted in Haranggaol Subdistric and Merek Subdistric at Province North Sumatera during four month from September until December. The objective of research is MPTS plant species be found in the catchment area Toba Lake. The data collection of secondary data, primary data, MPTS plant identification, literature reviews, interviews and direct observation in the field. The results research that be found 10 species of MPTS plant in the catchment area Toba Lake. MPTS is very beneficial for the people living in the Toba Lake catchment area both ecologically and economically. Peoples approved if the plant MPTS used as plant rehabilitation. Key word : Variaty, Deployment, Potential, Benefit, Plant Rehabilitation.